Guest editors’ introduction: Special issue on Inductive Logic Programming (ILP-2008) - Železný, Filip; Lavrač, Nada (Machine learning, 2009)
Issue Title: Special Issue: Inductive Logic Programming; Guest Editors: Filip elezný and Nada Lavrac